Hypothyroidism: Cardiovascular Endpoints of Thyroid Hormone Replacement - Angeliki Stamatouli; Pablo Bedoya; Sahzene Yavuz (Frontiers in Endocrinology, 2020)
Thyroid dysfunction, either thyrotoxicosis or hypothyroidism, represents an important cardiovascular risk factor. Heart disease is the leading cause of death for men and women in the United States. Cardiovascular disease is multifactorial and many efforts have been made to assess precipitants for optimal guideline-based, primary, and secondary prevention. Thyroid hormone receptors are present in the myocardium and endothelium, and small alterations in its levels could have significant effects in cardiac function. Specifically, overt hypothyroidism is associated with an increased risk for atherosclerotic cardiovascular disease due to metabolic and hemodynamic effects. Several concomitant factors like impaired lipid profile, low-grade chronic inflammatory state, increased oxidative stress and increased insulin resistance enforce this relationship. The last decade has seen a renewed interest on the impact of subclinical hypothyroidism on the cardiovascular system and whether or not it should be treated. The aim of this review is to provide current evidence of the effect of thyroid hormone replacement, either with levothyroxine mono-therapy or in combination with liothyronine, on specific cardiovascular parameters.